Spirit hermeneutics : reading scripture in light of Pentecost - Keener, Craig S., 1960- (Grand Rapids, MI, William B Eerdmans Publishing Company, 2016)
How do we hear the Spirit's voice in Scripture? Once we have done responsible exegesis, how may we expect the Spirit to apply the text to our lives and communities? In Spirit Hermeneutics biblical scholar Craig Keener addresses these questions, carefully articulating how the experience of the Spirit that empowered the church on the day of Pentecost can -- and should -- dynamically shape our reading of Scripture today. Keener considers what Spirit-guided interpretation means, explores implications of an epistemology of Word and Spirit for biblical hermeneutics, and shows how Scripture itself models an experiential appropriation of its message. Bridging the Word-Spirit gap between academic and experiential Christian approaches, Spirit Hermeneutics narrates a way of reading the Bible that is faithful both to the Spirit-inspired biblical text and the experience of the Spirit among believers. -- from book flap.
A theological reading toward praxis and mission -- Reading experientially -- Reading from the vantage of Pentecost -- Global readings -- Global reading : the Biblical model of Pentecost -- Global reading : contextualization and scripture -- Needing other cultures' input -- Some valuable majority world insights -- Connection with the designed sense -- The measuring stick -- Do ancient meanings matter? -- Room left for authors? -- Both-and -- Epistemology and the spirit -- An epistemology of word and spirit -- Biblical epistemology and hermeneutics -- Reading the Bible as truth -- Intrabiblical models for reading scripture -- How Jesus invites us to hear the Bible -- Reading the Torah as the law of faith -- Christological reading or personal application? -- Whose charismatic interpretation? -- Naive "Pentecostal" readings vs. biblically sensitive Pentecostal readings -- Global pentecostal community as a safety net? -- Scripture speaking personally -- and historically.
Includes bibliographical references (pages 389-457) and indexes.
Keywords: Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc; Holy Spirit; Pentecostalism; Holy Spirit; Pentecostalism; Criticism, interpretation, etc; Criticism, interpretation, etc